Evaluating the network traffic on an improved version of the Committeeless Proof-of-Stake blockchain consensus algorithm - Gigilas Junior, George; Ferreira, Filipe Franco; Henriques, Marco A. A. (Anais Estendidos do Simpósio Brasileiro de Cibersegurança (SBSeg); 2024: Anais Estendidos do XXIV Simpósio Brasileiro de Segurança da Informação e de Sistemas Computacionais, 2024)
Blockchain is a powerful way to store and process data in a decentralized way. Among its consensus algorithms, Committeeless Proof-of-Stake (CPoS) is a promising alternative to the better-known Proof-of-Work and Proof-of-Stake, with its reduced power consumption and more straightforward design without validation committees. However, CPoS is still an emerging algorithm and requires more testing to validate its correctness and efficiency. One of the problems it has to deal with is the higher network traffic compared to similar approaches due to the larger number of messages sent. This article aims to modify CPoS in order to reduce the data traffic and improve its performance.